PROFIL FLEKSIBILITAS PSIKOLOGIS SISWA DI SMA NEGERI 1 PAJAR BULAN - Roudhatul Hafizah; Alrefi (IKIP Siliwangi, 2026)
This study aims to describe the psychological flexibility profile of students at SMA Negeri 1 Pajar Bulan and examine gender differences. The study used a descriptive quantitative approach to objectively describe the students' psychological flexibility. The results showed that, in general, students' psychological flexibility was in the moderate category. This finding indicates that most students have demonstrated adequate adaptability in facing academic and social demands, but still require strengthening in aspects of emotional management, self-acceptance, and consistent action based on values. In terms of gender differences, female students tend to have higher psychological flexibility than male students. These results emphasize the importance of developing guidance and counseling services in schools that focus on increasing students' psychological flexibility to support their psychological resilience and mental well-being.